2018
DOI: 10.1093/nar/gky1238
|View full text |Cite
|
Sign up to set email alerts
|

Factor cooperation for chromosome discrimination inDrosophila

Abstract: Transcription regulators select their genomic binding sites from a large pool of similar, non-functional sequences. Although general principles that allow such discrimination are known, the complexity of DNA elements often precludes a prediction of functional sites. The process of dosage compensation in Drosophila allows exploring the rules underlying binding site selectivity. The male-specific-lethal (MSL) Dosage Compensation Complex (DCC) selectively binds to some 300 X chromosomal ‘Hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(88 citation statements)
references
References 72 publications
6
82
0
Order By: Relevance
“…To characterize the direct DNA binding of MSL2, DNA fragments from paired-end sequencing runs were computationally subset to sizes between 10 and 130 bp, i.e., sub-nucleosomal length, since it has been previously shown that HAS are nucleosome-free [8,12]. For clarity, we refer to those binding events as direct "DNA" binding ( Fig 2A).…”
Section: Chromatin Binding Of Msl2 Precedes Complete Dosage Compensationmentioning
confidence: 99%
See 2 more Smart Citations
“…To characterize the direct DNA binding of MSL2, DNA fragments from paired-end sequencing runs were computationally subset to sizes between 10 and 130 bp, i.e., sub-nucleosomal length, since it has been previously shown that HAS are nucleosome-free [8,12]. For clarity, we refer to those binding events as direct "DNA" binding ( Fig 2A).…”
Section: Chromatin Binding Of Msl2 Precedes Complete Dosage Compensationmentioning
confidence: 99%
“…Antibodies aMSL1, aMSL2, aMSL3, aMOF, and aMLE antibodies were previously described in Refs [12,[32][33][34]. aSXL antibody was kindly provided by F. Gebauer and previously described in Ref.…”
Section: Rna-seq Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We explored the interaction between the two recombinant complexes after expression from baculovirus vectors. Extracts containing JJ-complex (FLAG-JIL-1/untagged JASPer) on the one hand and a partial DCC consisting of MSL1, MSL2 and MSL3 (FLAG-MSL1/untagged MSL2/FLAG-MSL3) on the other hand were mixed in appropriate stoichiometry 45 and specific antibodies were used for immunoprecipitation (Supplementary Fig.8d). The MSL1 antibody retrieved not only the associated MSL2 and 3, but also some JJ-complex.…”
Section: Resultsmentioning
confidence: 99%
“…of MSL2 to DNA mediated by DNA shape(Albig et al 2019), specific threedimensional conformation surrounding CES(Ramírez et al 2015) , and 1.688 repetitive elements (Joshi and Meller 2017) . In the future, it will be possible to use the meiotic drive system to define the contribution of each of these factors to MSLc targeting in a developmental context.…”
mentioning
confidence: 99%